2022
DOI: 10.1002/ehf2.13964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS‐Cov‐2 infection in patients with hypertrophic cardiomyopathy: results of an international multicentre registry

Abstract: AimsTo describe the natural history of SARS-CoV-2 infection in patients with hypertrophic cardiomyopathy (HCM) compared with a control group and to identify predictors of adverse events. Methods and results Three hundred and five patients [age 56.6 ± 16.9 years old, 191 (62.6%) male patients] with HCM and SARS-Cov-2 infection were enrolled. The control group consisted of 91 131 infected individuals. Endpoints were (i) SARS-CoV-2 related mortality and (ii) severe clinical course [death or intensive care unit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Using high-resolution scRNA-seq, our results revealed the common gene expression changes of the HCM cardiomyocytes compared with other studies, 8,11 including the prominent up-regulation of NPPA, NPPB and biological pathways such as 'muscle contraction' and 'heart development'. Consistent with the previously reported elevated expression of ACE2 in HCM 14 and the potential link between HCM and COVID-19, 31 we showed that about 20 genes related to SARS-Cov-2 infection and immune response were up-regulated in HCM.…”
Section: Discussionsupporting
confidence: 92%
“…Using high-resolution scRNA-seq, our results revealed the common gene expression changes of the HCM cardiomyocytes compared with other studies, 8,11 including the prominent up-regulation of NPPA, NPPB and biological pathways such as 'muscle contraction' and 'heart development'. Consistent with the previously reported elevated expression of ACE2 in HCM 14 and the potential link between HCM and COVID-19, 31 we showed that about 20 genes related to SARS-Cov-2 infection and immune response were up-regulated in HCM.…”
Section: Discussionsupporting
confidence: 92%
“…Two smaller retrospective studies examining COVID-19 in HCM have also been reported. The first study examined 305 patients with HCM and SARS-CoV-2 infection and identified age, NYHA class, LVOT obstruction, and left-ventricular systolic diameter (LVSD) as factors driving mortality risk after multi-variate adjustment [26]. The same study compared mortality of patients with HCM and history of COVID-19 to control patients with history of COVID-19 and without HCM; the authors observed a 2.4-fold increase in mortality and 1.7-fold increase in hospitalization when adjusting for age and sex [26].…”
Section: Resultsmentioning
confidence: 99%
“…The first study examined 305 patients with HCM and SARS-CoV-2 infection and identified age, NYHA class, LVOT obstruction, and left-ventricular systolic diameter (LVSD) as factors driving mortality risk after multi-variate adjustment [26]. The same study compared mortality of patients with HCM and history of COVID-19 to control patients with history of COVID-19 and without HCM; the authors observed a 2.4-fold increase in mortality and 1.7-fold increase in hospitalization when adjusting for age and sex [26]. The second study described the clinical context of 70 patients with HCM and history of a positive SARS-CoV-2 test from a large urban hospital system in New York between January 2020 and January 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Heart failure (HF) presents progressive detrimental changes in cardiac structure and performance, an increase in left ventricular (LV) filling pressure (LVFP), impairment of quality of life, and adverse cardiovascular and systemic outcomes 1,2 . In addition to conventional risk factors, emerging non‐medical variables, such as the global epidemic of infectious diseases, climate change, and civil war, render HF patients vulnerable to rapid deterioration and adverse outcomes 3–5 . Risk classification is critical for the management of both clinical and at‐risk HF populations considering the tremendous medical and social burdens of HF 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to conventional risk factors, emerging non-medical variables, such as the global epidemic of infectious diseases, climate change, and civil war, render HF patients vulnerable to rapid deterioration and adverse outcomes. [3][4][5] Risk classification is critical for the management of both clinical and at-risk HF populations considering the tremendous medical and social burdens of HF. [6][7][8][9] Structural remodelling and functional derangement of cardiac chambers are directly related to unfavourable clinical outcomes in patients with HF.…”
Section: Introductionmentioning
confidence: 99%